Annona muricata in modern medicine and its broad spectrum therapeutic potential - Wiecanowska, Julia; Muszalska, Aleksandra; Roczyński, Brajan (Quality in Sport, 2026)
Background: Bioactive compounds from plants have gained significant attention in modern medicine, demonstrating therapeutic potential in cardiovascular, dermatological and oncological conditions. Annona muricata is a candidate with documented multidirection therapeutic potential, especially when it comes to acetogenins. Aim of the study: This review evaluates the status of Annona muricata (Graviola) in modern medicine, analyzes characteristics of the plant and its phytochemicals with their multidirectional activities, such as anticancer, antidiabetic and antinflammatory. Materials and methods: A systematic review of PubMed (last 20 years) was conducted using the keywords: „Annona muricata”, „bioactive compounds”. Conclusions: A. muricata’s extract demonstrates anticancer, antidiabetic, antioxidant and gastroprotective effects through mechanisms like oxidative stress modulation, apoptosis, cellular signalling pathways, inflammation. Anticancer activity has been the most studied. A. muricata represents a promising pharmaceutical, but further clinical studies are needed to establish its efficacy, safety and pharmacokinetic profile.